2023
DOI: 10.3390/molecules28155695
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of Gramine: Chemistry and Biological Activity

Abstract: The natural alkaloid gramine has attracted significant attention in both academic and industrial circles because of its potential and diverse biological activities, including antiviral, antibacterial, antifungal, anti-inflammatory and antitumor activities; application in therapy for Alzheimer’s disease; serotonin-receptor-related activity; insecticidal activity; and application as an algicide. In this review, we focus on the research advances that have been made for gramine-based molecules since their discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…38,39 GRM, a natural alkaloid obtained from Gramineae plants, has a wide application for pest control and drug development. 40,41 The alkaloid has been reported to be extensively present in agricultural land and groundwater. 17,18 Acute mortality of domestic animals has occurred through consumption of plants containing this compound.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 GRM, a natural alkaloid obtained from Gramineae plants, has a wide application for pest control and drug development. 40,41 The alkaloid has been reported to be extensively present in agricultural land and groundwater. 17,18 Acute mortality of domestic animals has occurred through consumption of plants containing this compound.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Plant-derived allelopathic compounds have become new generation pesticides, thereby reducing the environmental stress caused by synthetic chemicals. , As a result, the secondary metabolites produced by plants are widely distributed in aquatic environments and land. , Some are toxic and have harmful effects on organisms in the environment. , GRM, a natural alkaloid obtained from Gramineae plants, has a wide application for pest control and drug development. , The alkaloid has been reported to be extensively present in agricultural land and groundwater. , Acute mortality of domestic animals has occurred through consumption of plants containing this compound. , The resistance of GRM to degradation has a negative impact on human health. Elucidation of the mechanism of hepatotoxicity caused by exposure to GRM is of great significance.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various compounds identified in the alkaloidal extract (AAA), gramine, a simple indole alkaloid, was found to have the highest percentage peak area of all the phytocompounds. Gramine has recently gained prominence due to its diverse biological activities, which include insecticidal, antibacterial, antiviral, antitumor, and anti-inflammatory properties [ 46 ]. It may be suggested that the antiplasmodial effects of the AAA extract in this study are largely due to the intrinsic indole alkaloids and isoquinoline alkaloids in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Gramine, a natural indole alkaloid existing in higher plants, can be obtained by the Mannich reaction of indole . The classical Somei–Kametani reaction, which is widely used for the total synthesis of natural products, achieves the deaminative coupling of gramines with active carbon nucleophiles such as nitroalkanes, malonates, and cyanides in the presence of n -Bu 3 P as an activating reagent (Scheme a). , Later, ethyl propiolate and 2-chloro-4,6-dimethoxy-1,3,5-triazine (CDMT) were respectively reported as activating reagents for the deaminative coupling of gramines with active methylene carbon nucleophiles (Scheme b). , There were also sporadic reports on the deaminative coupling of gramines with sp 2 carbon nucleophiles (Scheme c) .…”
Section: Indroductionmentioning
confidence: 99%